The Biginelli Reaction with an Imidazolium–Tagged Recyclable Iron Catalyst: Kinetics, Mechanism, and Antitumoral Activity. Issue 13 (4th March 2013) - Ramos, Luciana M.; Guido, Bruna C.; Nobrega, Catharine C.; Corrêa, José R.; Silva, Rafael G.; de Oliveira, Heibbe C. B.; Gomes, Alexandre F.; Gozzo, Fábio C.; Neto, Brenno A. D.
Abstract The present work describes the synthesis, characterization, and application of a new ion‐tagged iron catalyst. The catalyst was employed in the Biginelli reaction with impressive performance. High yields have been achieved when the reaction was carried out in imidazolium‐based ionic liquids (BMI⋅PF6, BMI⋅NTf2, and BMI⋅BF4), thus showing that the ionic‐liquid effects play a role in the reaction. Moreover, the ion‐tagged catalyst could be recovered and reused up to eight times without any noticeable loss in activity. Mechanistic studies performed by using high‐resolution electrospray‐ionization quadrupole‐time‐of‐flight mass (HR‐EI‐QTOF) spectrometry and kinetic experiments indicate only one reaction pathway and rule out the other two possibilities under the development conditions. The theoretical calculations are in accordance with the proposed mechanism of action of the iron catalyst. Finally, the 37 dihydropyrimidinone derivatives, products of the Biginelli reaction, had their cytotoxicity evaluated in assays against MCF‐7 cancer cell linages with encouraging results of some derivatives, which were virtually non‐toxic against healthy cell linages (fibroblasts).